M3 receptor modulates extracellular matrix synthesis via ERK1/2 signaling pathway in human bladder smooth muscle cells. Issue 11 (17th February 2020) - Chen, Shulian; Liao, Banghua; Jin, Xi; Wei, Tangqiang; He, Qing; Lin, Yifei; Ai, Jianzhong; Gong, Lina; Li, Hong; Wang, Kunjie
Abstract: Extracellular matrix (ECM) accumulation plays a key role in the progression of bladder outlet obstruction (BOO). Muscarinic receptors have been widely reported to serve as pivotal regulators in lung tissue remodeling. However, the influence of them on human bladder smooth muscle cells (HBSMCs) and the underlying molecular mechanisms have not yet been evaluated. The purposes of the present study are to investigate the effect of muscarinic receptors on the synthesis of ECM in HBSMCs and the involvement of intracellular signal transducers. The results indicated that M1 ‐M5 muscarinic receptors were all encoded in HBSMCs. The expression rank order was M2 > M1 > M5 > M3 > M4 . The gene and protein expression of collagen I (COL1), TIMP‐1, and TIMP‐2 was carbachol (CCH) concentration‐dependently enhanced. The synthesis of COL1 in the supernatant of cell culture medium was significantly elevated by exposure to CCH. The CCH‐induced protein expression of COL1, TIMP‐1, and TIMP‐2, however, was obviously reduced by the pretreatment of muscarinic receptor antagonists, atropine, and M3 ‐preferring antagonist (1, 1‐dimethyl‐4‐diphenyl‐acetoxypiperidinium iodide [4‐DAMP]). Furthermore, ERK1/2 was activated by 100 µM CCH when compared with the control group and the pretreatment of ERK1/2 inhibitor significantly suppressed the synthesis of COL1 induced by 100 µM CCH. Besides, CCH‐induced phosphorylation of ERK1/2 was remarkably restrained by the pretreatment of 4‐DAMP. All in all, these findings demonstrated that M3 receptor can modulate extracellular matrix synthesis via the ERK1/2 signaling pathway, which may provide potential novel therapeutic targets for BOO. Abstract : Our study found that in human bladder smooth muscle cells, M3 receptor may not only modulate the smooth muscle cell contraction or proliferation but additionally have a role in the regulation of extracellular matrix (ECM) deposition. This might provide a novel molecular framework how ECM deposition in the context of bladder outlet obstruction and offer potential intervention targets to mitigate this pathophysiological process.